THE METAMORPHOSIS?: JHUMPA LAHIRI AND HER EXOPHONIC WRITING - Costa, Andrea Moraes da [UNESP] (Univ Estadual Mato Grosso Sul, 2022)
This article discusses the exophonic writing of Jhumpa Lahiri, a writer born in Great Britain, daughter of Indians and naturalized North American. Lahiri began her solid literary career writing in the English language and, in 2015, launched In Altre Parole, her first publication in the Italian language. This is a set of essays presenting the author's reflections on her fascination with Italian, her process of acquiring this language and her feeling of identity incompleteness, given her coexistence between Bengali and American cultures. Composing this set, La Metamorfosi stands out, an essay that constitutes the main point of this discussion and that will be debated based on its translation into English, published in 2017 under the title The Metamorphosis. In this essay, the author relies on Ovid's poem Metamorphoses to discuss her literary production in Italian, her own linguistic and literary metamorphosis or, as understood here, her exophonic writing. Thus, the article aims to demonstrate this author's perception of her practice. For this, the reflections on exophony presented in this text are based on studies by Chantal Wright (2008, 2013) on the subject.
Keywords: Exophony; In Altre Parole; In Other Words; Jhumpa Lahiri; The Metamorphosis